Morphological and anatomical characterization of yellow diploid potato flower for effective breeding program - de los Angeles Bohórquez-Quintero, María; Galvis-Tarazona, Daicy Yaneth; Arias-Moreno, Diana Marcela; Ojeda-Peréz, Zaida Zarely; Ochatt, Sergio; Rodríguez-Molano, Luis Ernesto (Scientific reports, 2022)
The diploid yellow potato ( Solanum tuberosum L. Phureja Group) is an important plant genetic resource. In this study, we report for the first time the characterization of anther development and pollen formation in the cultivar Criolla Colombia. The description of morphological and histological characters of buds and flowers at different developmental stages permitted to identify ten main stages, from the differentiation of the male cells of the sporangium, meiosis, microspores formation and maturation, to the release of mature pollen. In addition, the results provide a graphic guide of the development of the anther, through the sequential and orderly formation of the epidermis, the endothecium, the middle layer and the nutritive layer or tapetum. This microanatomical information will be useful for work focused on androgenesis and identification of gene regulation in floral biology and gamete formation. Therefore, this study determined that to efficiently obtain haploids, flower buds between 5 and 8.9 mm long (stage 6 to 8) should be used, in which tetrads and microspores are in the early uninucleate and binucleate stage.